Assessment of Ground‐Based X‐Band Radar Reflectivity: Attenuation Correction and its Comparison With Space‐Borne Radars Over the Western Ghats, India. Issue 11 (2nd November 2020) - Das, Subrata Kumar; Krishna, U. V. Murali; Kolte, Yogesh K.; Deshpande, Sachin M.; Pandithurai, G.
Abstract: Reflectivity measurements from X‐band ground‐based radar (GR) are assessed using observations from the Ku‐band space‐borne radars (SRs) onboard the Tropical Rainfall Measuring Mission and Global Precipitation Measurement satellites as a reference. The GR is at Mandhardev (18.04°N, 73.86°E) in the Western Ghats region, and the evaluation period is from June to September of 2014 and 2018. At X‐band, the rainfall‐induced attenuation leads to significant signal loss. The rain attenuation correction of GR is performed based on the relationship between specific attenuation and reflectivity. Using T‐matrix scattering simulations, the specific attenuation and reflectivity are derived from the disdrometer data. Further, the systematic differences between reflectivity measured by GR and SR are minimized by performing the frequency scaling using scattering simulation. The comparison between corrected reflectivities of GR and SR is achieved by matching the resolution volumes and viewing geometry of both radars. The evaluation between corrected reflectivities of GR and SR shows reasonable agreement between them, indicating that the attenuation correction performs reasonably for GR. In rain regions, the GR bias lies between −2.6 and −1.8 dB for stratiform cases, while for convective samples, the GR bias varies from −2.4 to −0.7 dB relative to SR observations. The GR shows smaller reflectivity compared to SR at all heights. This study aims to implement the attenuation correction to long‐term X‐band radar data available in the Western Ghats region to study the orographic precipitation and convective system during monsoon. Key Points: For the first time, assessment of reflectivities between IITM's X‐band radar and TRMM‐GPM Ku‐band radars is carried out The bias in GR attenuated corrected reflectivity is within −2.7 dB relative to SR measurements This study provides a framework to have attenuated corrected reflectivity for better quantitative application of reflectivity data